PENGARUH PERTUMBUHAN DANA PIHAK KETIGA (DPK), PERTUMBUHAN KREDIT, RISIKO KREDIT DAN PENGARUH FINANCIAL TECHNOLOGY TERHADAP PROFITABILITAS BANK KONVENSIONAL MASA PANDEMI COVID-19 - Novita Yenni Boang Manalu (2022)
THE EFFECT OF GROWTH OF THIRD-PARTY FUNDS, GROWTH OF CREDIT, CREDIT RISK AND THE EFFECT OF FINANCIAL TECHNOLOGY ON THE PROFITABILITY OF CONVENTIONAL BANKS DURING THE COVID-19 PANDEMIC By: Novita Yenni Boang Manalu Abstract This study aims to examine the effect of third-party funds, credit growth, credit risk, and financial technology on the profitability of conventional banks during the Covid-19 pandemic. The population in this study are conventional banks listed on the Indonesia Stock Exchange during the 2018-2021 period. The sample in this study consisted of 32 Banks, a period of 4 years, with 128 total samples. Sample was selected based on purposive sampling technique. In this study using secondary data obtained from financial statements in 2018-2021 using panel data regression analysis. The results of the study show that third party funds and credit growth have one significant effect on bank profitability, while credit risk has a negative effect on bank profitability, and financial technology has an effect on bank profitability. Keywords: Third Party Funds (DPK), Credit Growth, Credit Risk, Financial Technology.